2021
DOI: 10.1155/2021/8938530
|View full text |Cite
|
Sign up to set email alerts
|

Viral Zoonoses of National Importance in Ghana: Advancements and Opportunities for Enhancing Capacities for Early Detection and Response

Abstract: Zoonotic diseases have devastating impacts on human and animal health, livelihoods, and economies. Addressing the complex web of interrelated factors leading to zoonotic disease emergence and spread requires a transdisciplinary, cross-sectoral approach, One Health. The One Health approach, which considers the linkages between the health of people, animals, and their shared environment, presents opportunities to reduce these impacts through a more holistic coordinated strategy to understanding and mitigating di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 61 publications
(53 reference statements)
1
18
0
2
Order By: Relevance
“…Killing of suspected rabid dog and reporting to animal health officials were the most dominant practices as reported in Tanzania and Ethiopia [17,19] . The vaccination figures in this study compare better to those reported in Kenya [21] , Ethiopia [22] , and elsewhere in Ghana [8,13] . The high proportion of vaccinated dogs in this study can be traced to the free vaccination campaigns led by RIWA Ghana, considering that the majority of the vaccinations reported by this study happened at a RIWA Ghana campaign site, and only 1.5% of previous vaccinations happened outside the period of the campaign.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Killing of suspected rabid dog and reporting to animal health officials were the most dominant practices as reported in Tanzania and Ethiopia [17,19] . The vaccination figures in this study compare better to those reported in Kenya [21] , Ethiopia [22] , and elsewhere in Ghana [8,13] . The high proportion of vaccinated dogs in this study can be traced to the free vaccination campaigns led by RIWA Ghana, considering that the majority of the vaccinations reported by this study happened at a RIWA Ghana campaign site, and only 1.5% of previous vaccinations happened outside the period of the campaign.…”
Section: Discussionsupporting
confidence: 70%
“…Unlike in the Western Region of Ghana, where schools and mass media are the predominant sources of rabies information [8] , a majority of respondents in this study traced their rabies knowledge to family, neighbours, and friends, and a similar pattern was observed in Tanzania [17] . This study found significant differences between the level of rabies knowledge and the source of rabies information.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Through that framework, the GHSA and Veterinary Services Directorate (VSD) have intensified efforts to strengthen the national surveillance laboratory systems for swift detection and response to prioritised zoonotic diseases. OH workforce capacity in Ghana is enhanced through the [16] Training Programmes in Epidemiology and Public Health Interventions Network (TEPHINET) in core areas like applied epidemiology, public health, and laboratory practice skills. Despite widespread support for the OH concept in Ghana, resource limitations, nonexistence of a clearly defined multisector operational framework, and inadequate collaboration among key governmental agencies impacts Ghana's ability to effectively mitigate or respond to infectious biosecurity threats.…”
Section: Current Situation Of One Health Policy In Selected Sub-saharan African Countriesmentioning
confidence: 99%
“…In Ghana, just like most Sub-Saharan Africa (SSA) countries, the ability to detect and control emerging and reemerging infectious diseases (ERIDs) from all fronts is still challenged since it has not yet formalized a national One Health policy [17] and barely account for human health considerations in land-use planning decisions with deficiencies in the veterinary infrastructure, expertise, diagnostic laboratories, and in surveillance capabilities across the country. us, the health security of Ghana will continue to be threatened since the preparedness and response capability of a country depend on the availability of such facilities.…”
Section: Introductionmentioning
confidence: 99%